Nonlinear Static Analysis of Ordinary Highway Bridges Considering Geometry and Material Uncertainties - Yilmaz, Mehmet Fatih (Fırat University, 2022)
Material properties are an initial critical step to correctly determine the structure's capacities. Although there are many uncertainties, with the help of the probabilistic approach, the structural components' material strength was determined deterministically. The assumptions made to determine the material strengths generate additional uncertainties in determining the strength of the structures. Nowadays, developing computer technologies enable the determination of the strength capacities of structures with probabilistic approaches that consider these uncertainties in designing structural components. For this reason, while the approaches followed in the regulations included completely deterministic analyses in the past, quasi-statistical methods are used today, and studies are carried out to develop entirely statistical approaches. Therefore, to determine the structure's actual behavior, the uncertainties in the structural components should be taken into account. However, a practical and up-to-date approach has not been developed yet, and the existing methods impose an extensive analytical and computational burden. In this study, an ordinary single-column bridge in Türkiye was considered. Furthermore, the moment-curvature relationship of the pier was simulated considering material uncertainties. In addition, the differences in column heights and span lengths were modeled with the help of the Monte-Carlo simulation. Incremental static analyses were performed, and the lateral load-carrying capacities of the bridge were simulated.

Yapısal kapasitenin belirlenmesinde ilk ve en önemli aşamalardan biri malzeme dayanımlarının belirlenmesidir. Bu kısımda bir çok bilinmeyenin yer almasına karşılık, olasılıksal yaklaşımlardan faydalanılarak malzeme özellikleri deterministik olarak elde edilebilmektedir. Bununla birlikte geliştirilen olasılık modellerinde kullanılan yaklaşımlar ilave belirsizliklerin ortaya çıkmasına neden olmaktadır. Günümüzde gelişen bilişim ve bilgisayar teknolojileri yardımı ile malzeme yönünden belirsizliklerin yapısal tasarımlarda dikkate alınması mümkün hale gelmektedir. Bu nedenle geçmişte yönetmelikler tamamen deterministik yaklaşımları içerirken, günümüzde yarı-deterministik yaklaşımları içermekte ve tam olasılıksal yaklaşımların geliştirilebilmesi için çalışmalar yürütülmektedir. Bütün bunlar yapının performansının belirlenmesinde, yukarıda bahsi geçen belirsizliklerin dikkate alınmasını gerekli kılmaktadır. Ancak halen pratik ve güncel bir hesap yöntemi geliştirilebilmiş değildir. Bu çalışma kapsamında Türkiye karayolu hatlarında yer alan tipik bir köprü türü ele alınmış. Köprü ayağının moment-eğrilik ilişkisi malzeme belirsizlikleri dikkate alınarak modellenmiştir. Ayrıca kolon yükseklikleri ve köprü açıklıklarındaki belirsizlikler de Monte-Carlo yaklaşımı ile modellenmiş, köprünün yatay yük taşıma kapasitesinin belirlenebilmesi için artımsal statik itme analizi gerçekleştirilmiştir.
Standart Karayolu Köprüsünün Geometri ve Malzeme Yönünden Belirsizlikleri Dikkate Alarak Doğrusal Olmayan Statik Analizi